Transformation of Public and Private Spaces: Instrumentality of Restrictions on the Use of Public Space During COVID 19 Pandemic - Evren Ülkeryıldız; Deniz Can Vural; Duygu Yıldız (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2020)
This study explores the changing nature of public and private spaces and their characteristics in our daily life during the COVID-19 pandemic. It focuses on the role of the COVID-19 pandemic on the transformation of our physical (i.e., spatial) and social environments. This transformation process of physical and social environments has been primarily driven by implementation the "coercive restrictions" on the use of public spaces. The implementation of coercive restrictions on the use of public spaces has been receiving “mixed reactions” from people in different countries all around the world. The research presented herein studies these observed “mixed reactions” by using the lens of “instrumentality”. The use of concept of instrumentality reveals the subtle operation of the transformation taking place in public and private places all around the world. The findings of this research open up a new perspective to question, analyse, and evaluate the "instrumentality" of imposing coercive restrictions on the transformation of public and private spaces.